Why Dilmas governmente cannot be classified as new developmentalist? - Curado, Marcelo (Brazilian Journal of Political Economy, 2017)
This paper examines the role of new developmentalist agenda for actions in the economic area of Dilma Rousseff’s government. The paper aims to contribute to the research area that examines the relevance of schools of economic thought to economic policy in Brazil. The central conclusion is that - despite the increase in the state intervention in the economy - we cannot argue that the new developmentalist agenda played an important role in Dilma Rousseff’s government. The absence of a "national development strategy" and essential elements of the new developmentalist macroeconomic policy support this conclusion. JEL Classification: N16; O11; O54.